Expression of classical human leukocyte antigen class I antigens, HLA‐E and HLA‐G, is adversely prognostic in pancreatic cancer patients. Issue 8 (9th July 2020) - Hiraoka, Nobuyoshi; Ino, Yoshinori; Hori, Shutaro; Yamazaki‐Itoh, Rie; Naito, Chie; Shimasaki, Mari; Esaki, Minoru; Nara, Satoshi; Kishi, Yoji; Shimada, Kazuaki; Nakamura, Naoya; Torigoe, Toshihiko; et al.
Abstract: The expression of classical human leukocyte antigen class I antigens (HLA‐I) on the surfaces of cancer cells allows cytotoxic T cells to recognize and eliminate these cells. Reduction or loss of HLA‐I is a mechanism of escape from antitumor immunity. The present study aimed to investigate the clinicopathological impacts of HLA‐I and non–classical HLA‐I antigens expressed on pancreatic ductal adenocarcinoma (PDAC) cells. We performed immunohistochemistry to detect expression of HLA‐I antigens in PDAC using 243 PDAC cases and examined their clinicopathological influences. We also investigated the expression of immune‐related genes to characterize PDAC tumor microenvironments. Lower expression of HLA‐I, found in 33% of PDAC cases, was significantly associated with longer overall survival. Higher expression of both HLA‐E and HLA‐G was significantly associated with shorter survival. Multivariate analyses revealed that higher expression of these three HLA‐I antigens was significantly correlated with shorter survival. Higher HLA‐I expression on PDAC cells was significantly correlated with higher expression of IFNG, which also correlated with PD1, PD‐L1 and PD‐L2 expression. In vitro assay revealed that interferon gamma (IFNγ) stimulation increased surface expression of HLA‐I in three PDAC cell lines. It also upregulated surface expression of HLA‐E, HLA‐G and immune checkpoint molecules, including PD‐L1 and PD‐L2. These results suggest that the higher expression of HLA‐I, HLA‐E and HLA‐G on PDAC cells is an unfavorable prognosticator. It is possible that IFNγ promotes a tolerant microenvironment by inducing immune checkpoint molecules in PDAC tissues with higher HLA‐I expression on PDAC cells. Abstract : human leukocyte antigen class I antigens (HLA‐I) are needed for T cells to recognize target cells. Here, we showed that higher HLA‐I expression on pancreatic cancer cells is associated with poor prognosis, where formation of the tolerant microenvironment may be involved in IFNγ.